THE POTENTIAL OF THE DEVELOPMENT OF THE PECINAN GLODOK AREA OF NINE PLACES AS A CULTURAL TOURISM IN CHINA - Rianto Rianto (Program Studi Hospitality dan Pariwisata, 2021)
Glodok China Town area is one of the majority ethnic Chinese populations. Glodok Chinatown is also one of the important trade and economic centers in Jakarta. This area is thick with Chinese values and culture from building architects and, the life of the Chinese people who live with trading reason to this day in this area.This research was carried out starting at the 2571 Cap Go Meh Festival in 2020 which was held at Pancoran China Town. Researchers conducted descriptive qualitative research and in the collection techniques conducted were interviews, observation and documentation. Interviews were conducted by interviewing several informants such as local government, business actors, tourists and the community. This research aims to get to know the Glodok Petak Sembilan Chinatown area and to know various views and evaluations of informants about this area.The government, business actors, the community and tourists agree and support the making of the Glodok Petak Sembilan Chinatown as Chinese cultural tourism in Jakarta. The positive impact is that the presence of tourists is able to enliven the area and make the area better known by the wider community and help the economy of the business community surrounding the area. However, the negative impact found was a traffic jam or lack of traffic order. With the high interest of tourist arrivals, the parking facilities provided are inadequate with existing tourists, this is also one of the causes of lack of orderly traffic in this region.